PERBEDAAN KEJADIAN REINFARK MIOKARD AKIBAT PENGGUNAAN ANTIKOAGULAN UFH DAN ENOXAPARIN PADA PASIEN STEMI : TINJAUAN PUSTAKA SISTEMATIS - Mawita Suanbani, (2020)
Conditions myocardial infarction with STEMI requires revascularization treatment immediately. Pharmacologically enoxaparin is better than UFH because it less activates platelets that can induce Heparin Induced Thrombocytopenia or HIT. This condition is potentially lethal and one of the complications is acute myocardial infarction. The method of this research used Systematic Review, a method used to gather relevant evidence in accordance with the pre-determined eligibility criteria to answer the research question that becomes focus of the researches. Journal quality assessments was using The Cochrane Collaboration‟s Tool for Assessing Risk of Bias. Total of 36.778 patients with STEMI received anticoagulant therapy, 18.395 patients were taking enoxaparin and 18.383 patients were taking UFH or heparin. Total 23.255 patients received other fibrinolytic therapy as initial management for STEMI, patients were then randomized to receive enoxaparin or heparin therapy. Enoxaparin was better in inhibiting coagulation cascade than UFH, it was effective in preventing HIT, and also had a longer half-life and be able to suppress the von Willebrand factor. There were significant difference in myocardial reinfarction due to application of anticoagulant UFH and enoxaparin regardless of initial treatment. Keyword : Myocardial infarction, LMWH, UFH